Acute and chronic finger injuries in ball sports - Chick, Grégoire (Sports and traumatology)
Neglected finger injuries may lead to chronic lesions that often have detrimental consequences for the practice of a ball sport, whether at a recreational level or at the top athlete level. The initial injury management is crucial. Depending on the type and the severity of the lesions, different people may get involved: the players themselves or their entourage, physiotherapists, club doctors, emergency physicians, family doctors, sports doctors or hand surgeons. Treatment is usually conservative: the long fingers require rapid mobilization to prevent stiffness and contrary to that, the thumb requires stability. Surgery may be necessary to reach these goals especially for athletes, because of the demands of their sport. Chronic lesions are also in part related to repeated trauma, requiring specialized long-term multidisciplinary treatment. They can often lead to the end of a sporting career, but also may limit the functionality of the fingers at the time of conversion. Dr Chick is Consultant Hand Surgeon in Hôpital de la Tour (Geneva) and Clinique de Genolier, Switzerland, and Visiting Surgeon in Aspetar, Orthopaedic and Sports Medicine Hospital, Doha, Qatar. Introduction - Ball sports injuries – Epidemiology - Ball sports : definition and types - Epidemiology of finger injuries - Functional anatomy - Hand functional anatomy - Surgical approaches of the hand and digits - Hand morphology and ball sports - Examination of the injured hand - Radiological investigations - When to order plain radiographs and what to look for in each type of injury - When to order specific radiological investigations - Severe hand injuries - Management of hand and finger injuries - Equipment of hand therapist (primary care and after care) - The role of the sports physician - When to seek the advice of a hand surgeon? - Regional versus general anesthesia - Acute finger injuries - Fractures - Dislocations - Tendon injuries - Fingernails and ball sports - Nerve injuries in continuity, transected or lacerated - Laceration and infections in the fingers - The athlete with a single swollen joint finger after a trauma: clinical perspective - Chronic finger injuries - Stiffness in the hand - Old tendon injuries - Chronic instability - Fracture's sequelae - Post traumatic osteoarthritis - Complications associated with hand surgery - Overuse conditions of the hand and fingers in ball sport - Rehabilitation and principles of injury prevention in ball sports - Rehabilitation for hand injuries in athletes - Orthopedic taping, bracing, wrapping, padding - Protective equipment - Appropriate training and prevention after injury - The disabled athlete in ball sports - Opinions: optimizing the management of hand injuries in top athletes: the benefit of a specific medico-surgical coordination - Who decides and guides the athlete? - The top level athlete and the surgeon - Interviews.